Comparison of Two Types of Staged Laparoscopic Orchiopexy for High Intra-Abdominal Testes in Children: A Retrospective Study From a Single Center - Liu, Jie; Tang, Rui; Wang, Xiao; Sui, Bangzhi; Jin, Zhiyuan; Xu, Xudong; Zhu, Qinghua; Chen, Jin; Ma, Honglong; Duan, Guangqi (Frontiers in Pediatrics, 2021)
Purpose: To evaluate the efficacy and safety of two-stage laparoscopic traction orchiopexy (Shehata technique) compared to Fowler-Stephens (F-S technique) for high intra-abdominal testes (IATs) in children. Patients and Methods: We performed a retrospective review of all children (< 14 years old) who underwent laparoscopic treatment of high IAT in the pediatric surgery center of Yijishan Hospital of Wannan Medical College from April 2016 to April 2020. Participants were divided into the Fowler-Stephens (F-S) group and Shehata group according to the surgical method. We collected the medical records of all children and analyzed them statistically. Results: In this study, 43 patients in our center received two-stage laparoscopic surgical treatment. The results showed that there were 23 high IATs in 22 patients in the F-S group and 22 IATs in 21 patients in the Shehata group. All patients completed the operation successfully. No significant difference in operation time was noted between the two groups. There was no significant difference in the testicular atrophy rate between the two groups (P = 0.323). The testicular retraction rate of the F-S group was greater than that of the Shehata group (P = 0.04). Conclusion: The results of this study indicate that the application of assisted laparoscopic testicular traction technology can effectively retain the main blood supply of the testis and vas deferens with a high survival rate and clear advantages. The preliminary results show that the Shehata technique is safe, reliable and effective in the treatment of high IAT in children.